Routledge handbook on gender in tourism
1 online resource
Keywords: "This comprehensive Handbook delves into the multifaceted dimensions of the role of gender in tourism, spanning education, research, and practice. With 40 international contributions from leading thinkers in the field, this book brings together diverse themes such as entrepreneurship, mobility, sustainability, and sexuality. In doing so it shatters traditional boundaries and dissects how gender influences perceptions, experiences, and opportunities, advocating for equality and challenging entrenched power dynamics. Informed by the United Nation's Gender Equality goals, this Handbook champions the potential of gender-aware tourism to reshape the world by fostering inclusivity, empowerment, and understanding. It adopts diverse insights, encompassing feminist and queer perspectives, challenging norms, and exploring marginalized voices. By dissecting gender in educational, entrepreneurial, and research contexts, it unveils hidden dynamics. This book empowers readers to grasp the breadth of gender's role and equips them with tools to foster equality and reshape the tourism landscape, while making suggestions to future research agendas. This book is intended for scholars, educators, researchers, government officials and practitioners in the fields of gender studies, tourism, education, entrepreneurship, employment, mobility, research, sustainability, and sexuality"--